Effectiveness of the full digital flow in the confection of implant-supported single prostheses and comparative analysis between two techniques: with an abutment or direct. Cross-sectional cohort. - Alves, Stephanie; Moreno de Freitas, Rubens; Sartori, Ivete Aparecida de Mattias (Brazilian Journal of Implantology and Health Sciences, 2024)
With technological advances in Dentistry, the search for more predictable, integrated, and agile planning and treatments increases. In Implantology, despite the digital flow being greatly encouraged, doubts remain about its technical success. Therefore, the aim of this clinical study was to evaluate the effectiveness of the full digital flow using two techniques for the fabrication of implant prostheses: with an abutment or direct to the implant, comparatively evaluating the time required for interproximal adjustment to adapt the crowns, occlusal adjustment, and the need to return to the laboratory for corrections. The sample consisted of 46 patients who underwent the installation of 75 implants, treated at the ILAPEO School of Dentistry surgical clinic. They were all over 18, of both sexes and received implants in single edentulous spaces that required rehabilitation with crowns. These patients were divided into two groups, with Group I (G1), comprising 27 patients (38 implants) who had received abutments at the time of surgery, and Group II (G2) comprising 28 patients (37 implants) who had received healing caps, with 9 patients in common in both groups. In G1, scan bodies adapted to the abutments were used. In G2, they were directly adapted to the implants. The cases were scanned and sent to the laboratory. When the crowns were installed, the prosthesis adjustment data was recorded (in seconds), as well as the need to return to the laboratory for adjustments and corrections. The data from the groups were compared using the Mann-Whitney non-parametric test. There were no statistical differences in terms of occlusal and proximal adjustment time. The need to return prosthetic work to the laboratory was compared between the groups using the chi-squared test. The GraphPad Prism 8 software (San Diego, CA, USA) was used for the statistical analysis, and all tests were applied at a significance level of 5%. Data analysis leads to the conclusion that digital flow made it possible to obtain satisfactory implant-supported single crowns in both groups. No differences were found between the two techniques regarding the time taken to adapt to the mouth and the need to return to the laboratory.